Broiler performance fed jatropha curcas seed meal detoxified by fermentation, physic and chemical treatments - Elizabeth Wina; B Tangendjaja; T Pasaribu; T Purwadaria (Indonesian Center for Animal Research and Development (ICARD), 2010)
Utilization of jatropha seed meal as a feed ingredient is limited by the presence of several anti nutritive and toxic compounds in the seed meal. The aim of this research is to evaluate feeding of jatropha seed meal detoxified using fermentation by two fungi and rumen microbes (as biological detoxification) and using a combination of chemical and physical treatments on broiler performance. One hundred seventy five chicks (7 days old) were used and were divided into 5 treatments in 7 replications and each replication in one cage consisted of 5 chicks. R1 was control feed (K) without jatropha seed meal., 2) R2 was feed with 4% of Jatropha seed meal fermented by Neurosphora sitophila (FNS), R3 was feed with 4% of Jatropha seed meal fermented by Aspergillus oryzae (FAS), R4 was feed with 4% of Jatropha seed meal fermented by rumen microbes and R5 with 4% of Jatropha seed meal treated by autoclaved, refluxed by hexane and soaked in methanol (OEHM). Treated feed was given for 14 days at the end of the feeding treatment, two chickens from each replication were slaughtered and organ weights were recorded. Body weight of chicken and feed conversion ratio were calculated. The rest of the chicken was fed commercial feed for the next 7 days (recovery periode). Chicken mortality was almost 0% but 1 chicken from FAS treatment died at the recovery period. Feed consumption was lower at fermented jatropha seed meal than control (K) or OEHM, resulted in lower body weight of chicken. The abdomen fat weight and organ weights especially pancreas or spleen resulted from treatment with jatropha were much lower than that of K. In the recovery period, body weight of chicken in the OEHM treatment was almost similar from that of control chicken. In conclusion, biological detoxification on BBJ was able to reduce chicken mortality but could not improve the daily gain higher than control treatment. The best method to detoxify jatropha seed meal was the combination of physical and chemical treatment (using autoclave, followed by hexane and methanol extractions). Key Words: Broilers, Jatropha Seed Meal, Detoxification, Fermentation